URGENSI MENDAFTARKAN MEREK SUATU PRODUK DALAM USAHA ATAU BISNIS - Allysa Faras Nabila Rizadian1; Leo Danuarta; Merianty Merianty; Rian Rahmattulloh; Shadan Aryansyah Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Intellectual Property Rights is something that is protected by law. This mark has been regulated in Law Number 15 of 2001 concerning Trademarks, the owner of the mark will obtain legal protection for his trademark after registering the trademark with the Directorate General of Intellectual Property Rights. Violation of a registered mark will give rise to the rights of the owner of the registered brand name. One example is the use of the name